Determinants of Local Revenue in West Nusa Tenggara Province - Alan Budi kusuma; Muhammad Gahfur Wibowo; Akmal Ihsan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The economic growth of a region can be seen from the contribution of increasing regional original income originating from sources of taxes, regional levies, regional property and other separated regional wealth management results, and other legitimate regional revenues. The Province of West Nusa Tenggara in the last few decades has shown a significant increase in local revenue. In this study, the impact of population, inflation, and Gross Regional Domestic Product (GRDP) on local revenue from 2010 to 2021 is explored. The Generalized Method of Moments (GMM) technique uses district or city annual data in a quantitative panel data regression model for the study. According to the findings of statistical studies, local own-source revenue is significantly positively affected by government spending, population, and gross regional product (GDP), but inflation-related price increases have a negligible impact on local revenue. The money supply determines the rate of inflation, the high rate of inflation is caused by the amount of money in circulation.